Heart Rate Variability during two Relaxation Techniques in Post-MI Men - Leonaite, A.; Vainoras, A. (Elektronika ir Elektrotechnika, 2010)
This study examines the short-term effect of two relaxation techniques on heart rate variability (HRV) in patients with ischemic heart disease. The focus of our work was on whether progressive muscular relaxation and body scan meditation produce any reliable changes of HRV and whether these changes are any different from those produced by a comparable period of just lying quietly. A computerized ECG analysis system “Kaunas-load”, developed by the Institute of Cardiology of Kaunas Medical University, was applied for 12-lead ECG recording and analysis. ECG was recorded with the patient lying quietly for 5 min before each performed technique, for 20 min during each relaxation activity and for 5 min after each performed technique. Participants listened via headphone to audio-recorded relaxation instructions. The changes in HRV were analyzed. The results indicate both similarities and differences in the HRV responses to different relaxing activities.